2016
DOI: 10.1002/ejic.201601074
|View full text |Cite
|
Sign up to set email alerts
|

Acylchalcogenourea Complexes of Silver(I)

Abstract: Acylthio- or acylselenoureas react with silver(I) oxide to form tetranuclear silver(I) complexes containing the deprotonated acylchalcogenourea ligands bound to the silver atoms through the chalcogen and oxygen atoms. These tetrasilver(I) species react with either 4 or 8 equiv. of a phosphine to afford either dinuclear silver(I) phosphine complexes or tetrahedral silver diphosphine complexes. In these compounds, the acylchalcogenourea ligands form six-membered rings by coordinating to the metal atom through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Initially, we examined three different routes towards the desired NHC-gold(I) acylchalcogenoureato complexes: (1) the reaction of the acylchalcogenoureas with [AuCl(IPr)] [IPr = 1,3-di(2,6diisopropylphenyl)imidazolylidene] in the presence of base, (2) the reaction of the acylchalcogenoureas with [AuOH(IPr)] and (3) by transmetallation of [AuCl(IPr)] with the corresponding silver(I) acylchalcogenoureato complexes. 17 To our surprise, the latter two routes afforded either no products at all or we observed formation of dark, inseparable mixtures. In particular, the lack of reactivity of the gold(I) hydroxy complex [AuOH(IPr)] in this system is somewhat unexpected.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Initially, we examined three different routes towards the desired NHC-gold(I) acylchalcogenoureato complexes: (1) the reaction of the acylchalcogenoureas with [AuCl(IPr)] [IPr = 1,3-di(2,6diisopropylphenyl)imidazolylidene] in the presence of base, (2) the reaction of the acylchalcogenoureas with [AuOH(IPr)] and (3) by transmetallation of [AuCl(IPr)] with the corresponding silver(I) acylchalcogenoureato complexes. 17 To our surprise, the latter two routes afforded either no products at all or we observed formation of dark, inseparable mixtures. In particular, the lack of reactivity of the gold(I) hydroxy complex [AuOH(IPr)] in this system is somewhat unexpected.…”
Section: Resultsmentioning
confidence: 61%
“…We have previously reported the first Ag + and Au + compounds containing acylselenoureato and acylthioureato ligands together with a detailed study of their biological activity. [16][17][18][19] We also demonstrated that square planar gold(III) complexes with acylselenoureato ligands are accessible when a dicarbanionic co-ligand is present. 20 This stabilizing co-ligand is essential to prevent reduction of gold by the acylselenourea during the reaction.…”
Section: Introductionmentioning
confidence: 67%
“…1d (Figure b–d). These results meant that the single peak might be derived from the higher aggregation state B of complex A . Subsequently, when iminoester 2a was added to the complex solution (a), (c) and (d), respectively, we found the two doublet peaks of the Ag- 1d (1:1) complex A was easily moved to a new position at 31.88 ppm compared with the single peak of aggregated form B (Figure e–g).…”
mentioning
confidence: 84%
“…7a). 80 These clusters react with four or eight equivalents of a phosphine affording dinuclear Ag 81 The presence of the co-ligands is essential in this case to stabilise the copper(I) oxidation state.…”
Section: Methodsmentioning
confidence: 99%